2014
DOI: 10.1371/journal.pone.0091413
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Serotype-Specific Antibodies Persist through Early Childhood after Infant Immunization: Follow-Up from a Randomized Controlled Trial

Abstract: BackgroundIn a previous UK multi-center randomized study 278 children received three doses of 7-valent (PCV-7) or 13-valent (PCV-13) pneumococcal conjugate vaccine at 2, 4 and 12 months of age. At 13 months of age, most of these children had pneumococcal serotype-specific IgG concentrations ≥0.35 µg/ml and opsonophagocytic assay (OPA) titers ≥8.MethodsChildren who had participated in the original study were enrolled again at 3.5 years of age. Persistence of immunity following infant immunization with either PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Long-term immunogenicity studies on CRM 197 -based PCVs have been largely based on PCV7, indicating that serum IgG levels against vaccine serotypes remained ≥0.35 µg/mL in the majority of children for at least 4 years after the booster. 5 6 In this study, trend lines predicted that IgG titres against the predominant nasopharyngeal isolates in 2010–2014 (19A and 19F) in this region could persist above 0.35 µg/mL for >10 years in both the 2+1 and 3+1 immunisation groups, but the antibody concentrations and the persistence for the rare serotype 7F were lower (<3 years) in both groups.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Long-term immunogenicity studies on CRM 197 -based PCVs have been largely based on PCV7, indicating that serum IgG levels against vaccine serotypes remained ≥0.35 µg/mL in the majority of children for at least 4 years after the booster. 5 6 In this study, trend lines predicted that IgG titres against the predominant nasopharyngeal isolates in 2010–2014 (19A and 19F) in this region could persist above 0.35 µg/mL for >10 years in both the 2+1 and 3+1 immunisation groups, but the antibody concentrations and the persistence for the rare serotype 7F were lower (<3 years) in both groups.…”
Section: Discussionmentioning
confidence: 59%
“… 7 Some clinical trials of PCVs also observed a robust immune response to one dose of PCV13 in previously immunised children aged 2–5 years. 5 8 …”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharide capsule of 19F is more resistant to complement deposition than 6B and requires higher levels of antibodies for opsonophagocytosis. 38 However, although trials 37,40,41 have shown persistence of serum antibodies several years after vaccination, the exact mechanism underlying the protection against acquisition of carriage remains unclear. Such mechanisms could perhaps involve mucosal immunological responses 42 in addition to preexisting circulating serum immunoglobulin (IgG), with serological markers incompletely capturing the mucosal response.…”
Section: Discussionmentioning
confidence: 99%
“…IgG levels and OPA titers at 24 months were largely determined by the amount of antibody detected 1 month post booster at 13 months of age, which has been previously demonstrated where the same PCV was used for both priming and boosting. 24 These findings suggest that boosting with a different vaccine containing the same capsular serotypes, albeit conjugated to different carrier proteins, induces an immune response that is not only driven by short-lived extrafollicular B cells but also the generation of long-lived plasma cells, a hallmark of immune memory.…”
mentioning
confidence: 93%